Social Media Influencers Source Credibility and Product Fit Impact on Customers Purchasing Intentions, Under the Moderating Effect of Gender, Malaysian Context - Shadah, Mohammad (Archives of Business Research, 2021)
This study seeks to identify the source credibility of social media influencers that impact customer’s purchase intention under the moderating effect of gender. It adopts the Ohanian model of sources credibility and Kamins, Michael A.’s "match-up" hypothesis. The conceptual model includes (purchase intention” source credibility” trustworthiness” attractiveness” expertise “gender and product match-up). The researchers employed online surveys to collect responses on the criteria in the current study, which took a quantitative approach, using convenience sampling techniques. A total of 231 responses were received after data cleaning, 209 responses were accepted. SmartPLS 3, were used for data analysis. The research findings show that expertise, attractiveness, and match-up are the key factors that influence customers’ purchase intention and describe the customer’s perception of influencers, except for trustworthiness, which suggests that Malaysian customers are aware of the authenticity issues of social media influencers. This study also revealed that there is no moderating effect across gender regarding social media influencers except for trustworthiness. The study has implications for general management as social media influencer has a powerful impact on effective communication and marketing strategies.